PENGARUH DEWAN DIREKSI, KOMISARIS INDEPENDEN, KEPEMILIKAN MANAJERIAL DAN KEPEMILIKAN INSTITUSIONAL TERHADAP KINERJA PERUSAHAAN DENGAN ENTERPRISE RISK MANAGEMENT SEBAGAI INTERVENING (Studi Empiris pada Perusahaan Manufaktur yang Terdaftar di Bursa Efek Indonesia Periode Tahun 2012-2014) - Lestari, Sri Rahayu; Sari, Ria Nelly; A, Al Azhar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
The purpose of this study is to examine the effect of Good Corpotare Governance’s mechanism that consist of Board of Directors, Independent Commissioner, Manajerial Ownership, and Institusional Ownership on the existence of Enterprise Risk Management and the effect of the Enterprise Risk Management on firm performance. In addition, this study also examines the intervening role of Enterprise Risk Management on the relationship between Corporate Governance and firm performance. The population of this study was manufacturing companies listed in Indonesia Stock Exchange for the 2012 to 2014 financial year. By using purposive sampling method, 25 firms were selected as a sample. This study used data from company’s annual report. The analysis technique used multiple linear regression analysis using SPSS computer program. The results of analysis showed that Board of Directors, Independent Commissioner, Manajerial Ownership, and Institusional Ownership affect the existence of Enterprise Risk Management and the existence Enterprise Risk Management affects firm performance. The result also proved that Enterprise Risk Management act as an intervening variable among Board of Directors, Independent Commissioner, Manajerial Ownership, and Institusional Ownership on firm performance.Keyword : Good Corporate Governance, Enterprise Risk Management and Firm Performance